Impacts of agricultural public spending on Chinese food economy: A general equilibrium approach - Zhang, Yumei; Xu, Shiwei; Diao, Xinshen; Chen, Kevin Z. (Emerald Publishing Limited, 2011)
The purpose of this paper is to develop a dynamic computable general equilibrium (DCGE) model to analyze economy‐wide impacts of different types of public spending in China. A particular focus is placed on their impacts on food economy.In this paper, DCGE model is developed to analyze economy‐wide impacts of different types of public spending in China. The effects of increased agricultural subsidies, agricultural R&D, and irrigation are simulated by using China DCGE model.The results show that public spending has significant impact on food production, price, and trade. The increased public spending on agricultural R&D, irrigation, and agricultural subsidy also has modest impacts on other sectors such as industry, service, and GDP growth.The paper constructs the China dynamic CGE model and analyzes economy‐wide impacts of different types of public spending in China, especially for the food economy.